Pengembangan Blog sebagai Media Pemasaran untuk UMKM Laundry Dua Putri - Reghina Syakhila; Della DelfiYanti; Nafisah Altin; Novadilastri; Sularno (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2024)
This study discusses the importance of online marketing for micro, small, and medium enterprises (MSMEs) in the digital era, focusing on Laundry Dua Putri in Padang City. The research employs interview methods to gather information from the business owner. The findings indicate that Laundry Dua Putri has significant potential to meet laundry service demands but has not fully utilized digital platforms. By developing a blog as a marketing medium, it is hoped that this MSME can enhance its visibility and competitiveness in the market. This project is also part of the Project Based Learning (PBL) activities for students of the Business Administration Program, aimed at providing practical experience in website design.